Moving from Warrior to Guardian: Informal Learning in Police and Community Relations - Kyle Znamenak; Catherine A. Hansman (Adult Education Research Conference, 2022)
This qualitative research explores the informal learning experiences of police officers that contributes to patrol officers' learning, knowledge, and skills in developing and sustaining community relations within urban contexts.
Keywords: informal learning; police training; community relations; urban contexts